Strategic Application Portfolio in SMEs* (Malaysian Management Journal, 2002)
This paper discusses the state of a small and medium enterprise's (SME) information needs in terms of its strategic application portfolio. Specifically, it examines the strategic information requirements of a manufacturing SME with the aim of understanding the application strategy needed to formulate the firm's IT adoption so that lessons could he learnt from such technology innovation. A case study approach was chosen in which information requirements of the firm were investigated. Analysis was done to examine the evidence of potential applications strategic to the .firm 's business mission, goals and functional requirements. Major deliverables include an enterprise-wide data model representing a high-level overview of the firm's information requirements, a business area classification, and portfolios of applications categorized according to strategic, operational, potential and support using the classical McFarlan and McKenney Strategic Importance Matrix.